Distribution of stream macroalgae in the eastern Atlantic Rainforest of São Paulo State, southeastern Brazil - Branco, Ciro Cesar Zanini [UNESP]; Necchi Jr., Orlando [UNESP] (Springer Nature, 1996)
Fifty-two stream segments were sampled from 16 August to 13 September in 1993 in the eastern Atlantic Rainforest of São Paulo State, southeastern Brazil (22°55′-25°00′S, 44°48′-48°03′W). Forty-two macroalgal subgeneric taxa were found and the most widespread species were Audouinella pygmaea (21% of sites), Compsopogon leptoclados and Microcoleus subtorulosus (19%). Macroalgal species number per sampling site ranged from 0 to six (2.6 ± 1.7) and was positively correlated to species abundance, whereas species cover ranged from 0 to 70% of the stream bed (15.5 ± 20.8%). No significant correlation was found among macroalgal species number and abundance with any physical or chemical variable analyzed. Most sites were dominated by one or few macroalgal species, mainly, Audouinella macrospora, C. leptoclados and M. subtorulosus. No significant difference was found between the frequency distribution of variables measured for streams and for total macroalgae but the most widespread species (A. pygmaea) differed significantly for current velocity, specific conductance, turbidity and pH. Overall means for macroalgal occurrence include the following values: temperature (X̄ = 19.9°C), current velocity (X̄ = 45 cm s-1), oxygen saturation (X̄ = 66%), specific conductance (X̄ = 59.6 μS cm-1), turbidity (X̄ = 5 NTU) and pH (X̄ = 7.1). This pattern of patchy distribution and dominance by few species has been suggested as typical of stream macroalgal communities and has been ascribed to the rapid fluctuation of physical and chemical conditions. Total macroalgal species richness as well as mean species number per sampling site were considerably lower than found in similar studies of other regions. The Intermediate Disturbance Hypothesis was applied to explain these results: the same factor (high precipitation) responsible for the maintainance of the high species diversity in the surrounding forest can be, paradoxically, a constraint to the development of a more diverse macroalgal flora in streams. © 1996 Kluwer Academic Publishers.
Keywords: Brazil; Distribution; Macroalgae; Periphyton; Rainforest; Stream; community composition; macroalgae; periphyton; physical environment; rainforest; stream; Brazil, Sao Paulo State; Audouinella pygmaea; Compsopogon leptoclados; Microcoleus subtorulosus